Effect of substitutional defects on resonant tunneling diodes based on armchair graphene and boron nitride nanoribbons lateral heterojunctions - Sanaeepur, Majid (Beilstein Journal of Nanotechnology, 2020)
A nanometer-scaled resonant tunneling diode based on lateral heterojunctions of armchair graphene and boron nitride nanoribbons, exhibiting negative differential resistance is proposed. Low-bandgap armchair graphene nanoribbons and high-bandgap armchair boron nitride nanoribbons are used to design the well and the barrier region, respectively. The effect of all possible substitutional defects (including BC, NC, CB, and CN) at the interface of graphene and boron nitride nanoribbons on the negative differential resistance behavior of the proposed resonant tunneling diode is investigated. Transport simulations are carried out in the framework of tight-binding Hamiltonians and non-equilibrium Green’s functions. The results show that a single substitutional defect at the interface of armchair graphene and boron nitride nanoribbons can dramatically affect the negative differential resistance behavior depending on its type and location in the structure.
Keywords: AGNR/ABNNR heterojunction; armchair boron nitride nanoribbon (ABNNR); armchair graphene nanoribbon (AGNR); negative differential resistance (NDR); nonequilibrium Green’s function (NEGF); resonant tunneling diode (RTD); substitutional defects